Can a Tobin tax curb speculation in the housing market? A study on the effect in the primary market of Hong Kong tax policy - DANG, Dinh Tuan (Institutional Knowledge at Singapore Management University, 2024)
This study examines the effect of Special Stamp Duty (SSD) and Buyer's Stamp Duty (BSD) on Hong Kong’s housing prices in the primary market. Using micro transaction data, I show that the Tobin tax policies were not effective in cooling the primary market. The primary market responded differently when facing the two events. Specifically, SSD Phase 1 led to a 9.4% price increase within 6 to 12 months post-implementation, suggesting a lag effect. The introduction of SSD Phase 2 and BSD initially caused a significant 13.1% price surge in the first 6 months, but was followed by a notable 9% decrease in the subsequent 6 to 12 months, indicating a market overreaction. I further show that the effect of the Tobin tax policies varied across different submarkets by size and location. The results are robust with a shorter pre-policy period analysis, the inclusion of an additional control variable, and placebo tests.